The 2016 January eruption of recurrent Nova LMC 1968. Issue 1 (23rd October 2019) - Kuin, N P M; Page, K L; Mróz, P; Darnley, M J; Shore, S N; Osborne, J P; Walter, F; Di Mille, F; Morrell, N; Munari, U; Bohlsen, T; Evans, A; et al.
ABSTRACT: We present a comprehensive review of all observations of the eclipsing recurrent Nova LMC 1968 in the Large Magellanic Cloud which was previously observed in eruption in 1968, 1990, 2002, 2010, and most recently in 2016. We derive a probable recurrence time of 6.2 ± 1.2 yr and provide the ephemerides of the eclipse. In the ultraviolet–optical–IR photometry the light curve shows high variability right from the first observation around 2 d after eruption. Therefore no colour changes can be substantiated. Outburst spectra from 2016 and 1990 are very similar and are dominated by H and He lines longward of 2000 Å. Interstellar reddening is found to be E ( B − V ) = 0.07 ± 0.01. The super soft X-ray luminosity is lower than the Eddington luminosity and the X-ray spectra suggest the mass of the white dwarf (WD) is larger than 1.3 M⊙ . Eclipses in the light curve suggest that the system is at high orbital inclination. On day 4 after the eruption a recombination wave was observed in Fe ii ultraviolet absorption lines. Narrow-line components are seen after day 6 and explained as being due to reionization of ejecta from a previous eruption. The UV spectrum varies with orbital phase, in particular a component of the He ii  1640 Å emission line, which leads us to propose that early-on the inner WD Roche lobe might be filled with a bound opaque medium prior to the re-formation of an accretion disc. Both this medium and the ejecta can cause the delay in the appearance of the soft X-ray source.